2022
DOI: 10.31234/osf.io/h9bmy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric evaluation of a visual interpersonal analogue scale

Abstract: Interpersonal theory organizes social behavior along dominant (vs. submissive) and warm (vs. cold) dimensions. There is a growing interest in assessing these behaviors in naturalistic settings to maximize ecological validity and to study dynamic social processes. Studies that have assessed interpersonal behavior in daily life have primarily relied on behavioral checklists. Although checklists have advantages, they are discrepant with techniques used to capture constructs typically assessed alongside warmth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In other words, when participants were highly satisfied, the instrument seemed less able to reflect differences in the latent variable as participants may have reached the limit of the response scale. This might be a restriction of the seven-point Likert scale and could be addressed by using a visual analog scale instead (e.g., Woods et al, 2022). Third, our findings show that invariance of the measurement model should not be taken for granted when assessing momentary satisfaction.…”
Section: Summary and Discussion Of The Step 3 Applicationmentioning
confidence: 90%
“…In other words, when participants were highly satisfied, the instrument seemed less able to reflect differences in the latent variable as participants may have reached the limit of the response scale. This might be a restriction of the seven-point Likert scale and could be addressed by using a visual analog scale instead (e.g., Woods et al, 2022). Third, our findings show that invariance of the measurement model should not be taken for granted when assessing momentary satisfaction.…”
Section: Summary and Discussion Of The Step 3 Applicationmentioning
confidence: 90%
“…For both self and informant ratings, the pole scale scores were then used to calculate level of dominance by subtracting Submissiveness from Dominance and affiliation by subtracting Quarrelsomeness from Agreeableness. Other work using the SBI has shown that average momentary dominance correlates with cross-sectional dominance and lower neuroticism and that average momentary affiliation correlates with cross-sectional affiliation, submissiveness, agreeableness, and lower neuroticism (Côté, & Moskowitz, 1998; Woods et al, in press). In addition, variability in dominance and affiliation correlates with cross-sectional interpersonal problems, lower relationship satisfaction, and higher anxiety and depression (Erikson et al, 2009; Rappaport et al, 2014; Sadikaj et al, 2015).…”
Section: Methodsmentioning
confidence: 97%
“…Next, they were asked to rate the interpersonal behaviors of themselves and the person with whom they interacted using the Visual Interpersonal Analogue Scale (VIAS, Woods et al, 2020), which includes two sliding bars of interpersonal warmth (ranging from Cold/Distant/ Hostile [−5] to extremely Warm/Friendly/Caring [5]) and interpersonal dominance (ranging from extremely Accommodating/Submissive/Timid [−5] to Assertive/ Dominant/Controlling [5]). Individuals' ratings of their own interpersonal behaviors were not used in the current study.…”
Section: Interpersonal Behaviorsmentioning
confidence: 99%